COMMUNITY RESPONSE (CRM)-BASED PRIORITY SCALE SYSTEM FOR TRANSJAKARTA ROUTE REPAIR in DKI JAKARTA PROVINCE - Hairrudin; Agus Suroso (Jurnal Pensil)
This research aims to develop a priority scale system (PSS-TJ) based on Quick Community Response (QCR) for effective and efficient improvements to the TransJakarta route. Using aqualitative approaches with a case study in DKI Jakarta over 6 months, this research involved in- depth interviews with key stakeholders, fields observations of infrastructure conditions, and secondary data analysis from 13 official complaints channels. The research results identified six main criteria for priorities repairs, with the highest weights being the type of crack (0.25) and the width of the crack (0.20). The Road Damage Index (RDI) mathematical model was developed for an objectives assessment of the level of road damage, with Corridor 13 having the highest Road Damage Index (RDI) score (15), indicating the most urgent repairs needs. The integration of CRM data in decision making has been proven to increase the accuracy and responsiveness of TransJakarta infrastructure management. This system has the potential to significantly improve the quality of TransJakarta services, with a projected increase in travel time efficiency of up to 15% and user satisfaction of 20%. Furthermore, this Community Response (QCR) based priority scale system (PSS-TJ) can be an innovative model for Transjakarta road improvement systems in other cities in Indonesia, enabling resources optimization and increasing public participation in urban transportation infrastructure management.